Measuring. Monitoring. Management. Control - E.A. Pecherskaya; O.V. Karpanin; D.E. Nelyutskovа; A.M. Metalnikov; U.S. Chikhrina (Измерение, мониторинг, управление, контроль)
Background. Currently, semiconductor structures and devices are used in many industries, in particular electronics, telecommunications, and instrumentation. This article discusses a method for experimentally determining their parameters by measuring the volt-ampere characteristics of semiconductors using an automated information and measurement system. The purpose of the work is to study the electrophysical parameters of semiconductor components and describe the measurement technique used as the basis of the measuring system. Materials and methods. The automated information and measurement system is designed to study various semiconductor components and products, such asintegrated circuits, microcircuits, diodes, transistors, solar cells, zener diodes, charge-coupled devices, solar cells. All these components are used in electronics, mechanical engineering, optoelectronics and signal processing systems. Results. The volt-ampere characteristic was measured using the example of a semiconductor component (diode 2D212B), and the results obtained were analyzed, presented in tabular and graphical form. Conclusions. The structure of an automated information and measurement system is presented, which contains a measuring unit and a computer that controls measurements and automated processing of measurement results in order to determine the electrophysical parameters of the structures under study according to the measured volt-ampere characteristic.